FASHION MICRO - INFLUENCER’S ATTRIBUTIONS ON INSTAGRAM REELS, ATTITUDES AND PURCHASE INTENTION OF MILLENNIALS - Omnok, Sujittra; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of MCU Nakhondhat, 2024)
The Objectives of this research paper were 1) Study the Instagram Reels usage micro - influencers attributions Attitudes and purchase intention of millennial consumers. 2) Study the relationship of Instagram Reels usage fashion micro-influencers attributions Attitudes towards micro - influencers and purchase intention of millennial consumers. Study the fashion micro - influencers attributions Attitudes and purchase intention of millennial consumers. the study was conducted as a survey study, with a sample of 400 millennials selected through a convenient sampling technique. The collected data were analyzed using both descriptive and inferential statistics. However, variations in education levels and occupation induced differences in purchase intention of millennials. The use of Instagram Reels exhibited a positive correlation with millennials purchase intention, with statistical significance at the .05 level. Moreover, fashion micro-influencers attributions demonstrated a positive correlation with millennials’ purchase intention at a significance level of .05. Attitudes toward fashion micro -influencers on Instagram Reels were also positively linked to millennials’ purchase intention with statistical significance at .05. Ultimately, the usage of Instagram Reels and attributions of and attitudes toward fashion micro - influencers collectively influencer millennials’ purchase intention in the fashion domain, with statistical significance at the .05 level.